Ocena występowania wad stóp u dzieci w wieku 9-10 lat w środowisku miejskim i wiejskim = Estimate the prevalence the feet defects in children aged 9-10 years in the urban and rural environment - Anna Plaskiewicz; Krystian Kałużny; Bartosz Kochański; Łukasz Wołowiec; Wojciech Hagner; Walery Zukow (Kazimierz Wielki University, 2015)
Plaskiewicz Anna, Kałużny Krystian, Kochański Bartosz, Wołowiec Łukasz, Hagner Wojciech, Zukow Walery. Ocena występowania wad stóp u dzieci w wieku 9-10 lat w środowisku miejskim i wiejskim = Estimate the prevalence the feet defects in children aged 9-10 years in the urban and rural environment. Journal of Education, Health and Sport. 2015;5(4):325-334. ISSN 2391-8306. DOI: 10.5281/zenodo.17211 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A325-334 https://pbn.nauka.gov.pl/works/556080 http://dx.doi.org/10.5281/zenodo.17211 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 10.04.2015.   Ocena występowania wad stóp u dzieci w wieku 9-10 lat w środowisku miejskim i wiejskim Estimate the prevalence the feet defects in children aged 9-10 years in the urban and rural environment   Anna Plaskiewicz1, Krystian Kałużny1, Bartosz Kochański1, Łukasz Wołowiec2, Wojciech Hagner1, Walery Zukow3   1) Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 2) Studenckie Koło Naukowe Diagnostyki i Terapii Niewydolności Serca, II Katedra Kardiologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 3) Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy   Streszczenie   Wstęp. Wady stóp u dzieci są powszechnym problemem medyczno-społecznym w Polsce i na Świecie. Styl i szybkie tempo życia współczesnego człowieka wpływają niekorzystnie na postawę ciała, a stopy są szczególnie narażone na niekorzystny wpływ działania czynników środowiska zewnętrznego. Cel pracy. Celem pracy jest ocena występowania wad stóp u dzieci w wieku 9-10 lat w środowisku miejskim i wiejskim. Materiał i metody. Badaniami objęto grupę 40 dzieci w wieku 9-10 lat. Ze względu na miejsce zamieszkania dzieci podzielono na dwie grupy. Analizę stóp wykonano metodą platurograficzną polegającą na sporządzeniu odcisków podporowej powierzchni stopy. Oceniano wskaźniki opisujące wady stóp tj: wskaźnik "Ky" Sztritera-Godunowa, wskaźnik kątowy Clarke'a (CI), wskaźnik Wejsfloga, kąt piętowy oraz kąt koślawości palucha. Wyniki. Wśród przebadanych dzieci najczęstszą wadą stóp było płaskostopie. Zaobserwowano minimalnie mniej wad stóp u dzieci ze wsi w porównaniu z dziećmi mieszkającymi w mieście, jednak różnice nie są istotne statystycznie. Nie zaobserwowano różnic związanych z występowaniem wad stóp pomiędzy dziećmi ze wsi i z miasta. Wnioski. 1. Większość dzieci zarówno z miasta (65%) jak i ze wsi (75%) ma prawidłowo ukształtowane stopy. 2. Najczęstszą wadą stóp występującą wśród przebadanych dzieci jest płaskostopie. 3. Nie zaobserwowano istotnych różnic statystycznych w ocenie stóp pomiędzy dziećmi mieszkającymi w środowisku miejskim i wiejskim.   Abstract   Introduction. Feet defects in children is a common socio-medical problem in Poland and the world. Lifestyle of modern man adversely affect posture. The feet are particularly vulnerable to the adverse effects factors the external environment. Aim of the study. The aim of the study is to estimate the prevalence the feet defects in children aged 9-10 years in the urban and rural environment. Materials and methods. The study was conducted on 40 children aged 9-10 years. The children were divided into two groups according to their place of residence. Analysis of the feet were an approach to the preparation of the supporting surface of the feet prints. Evaluated indicators describing defects the feet: Sztriter-Godunov indicator, Clarke angle (CI), the Wejsflog indicator, heel angle and hallux valgus angle. Results. The most common feet defect of tested children is flat feet. Marginally less feet defect was observed in children from rural areas than in children from the city - however, the differences are not statistically significant. There is no difference associated with the presence of feet defects between children from urban and rural environment. Conclusions. 1. Most of the children, both from the city (65%) and from rural areas (75%) have a properly constructed foot. 2. The most common defect of feet among tested children is flat feet. 3. There were no statistically significant differences in the assessment of feet between children living in urban and rural environments.   Słowa kluczowe: wady stóp, środowisko wiejskie, środowisko miejskie, dzieci.   Keywords: feet defects, urban environment, rural environment, children.